Recurrence and prognosis of patients emergently hospitalized for acute esophageal variceal bleeding: A long‐term cohort study. Issue 13 (16th May 2016) - Cho, Hourin; Nagata, Naoyoshi; Shimbo, Takuro; Sakurai, Toshiyuki; Sekine, Katsunori; Okubo, Hidetaka; Imbe, Koh; Watanabe, Kazuhiro; Mikami, Shintaro; Yokoi, Chizu; Kobayakawa, Masao; Mizokami, Masashi; et al.
Abstract : Aim: To elucidate the rates of recurrence and mortality in acute esophageal variceal bleeding and the associated risk factors. Methods: A cohort of 174 patients emergently hospitalized for esophageal variceal bleeding was analyzed. All patients underwent endoscopic variceal ligation within 3 h of arrival. Comorbidities, vital signs, drug use, laboratory data, etiology, endoscopic findings, transfusion requirement, and follow‐up endoscopy were assessed. Cox's proportional hazards model was used to estimate hazard ratios (HR). Results: Rebleeding was identified in 49 patients with a mean follow‐up of 18 months. The cumulative rebleeding rate at 1 month, 1 year, and 5 years was 10.2%, 30.0%, and 51.0%, respectively. In multivariate analysis, independent risk factors for rebleeding were child‐Pugh class C (HR 1.94; P = 0.027), alcoholic liver cirrhosis (HR 2.32; P = 0.01), and no follow‐up endoscopy (HR 13.3; P < 0.001). During the overall mean follow‐up of 22 months, 69 patients died (17 due to bleeding), and the cumulative mortality rate at 1 month, 1 year, and 5 years was 12.2%, 26.6%, and 63.0%, respectively. In multivariate analysis, independent risk factors for mortality were child‐Pugh class C (HR 2.91; P < 0.001), coexistence of hepatocellular carcinoma (HR 1.92; P = 0.013), and no follow‐up endoscopy (HR 23.6; P < 0.001). Conclusion: This study revealed more than 50% cumulative rebleeding and mortality in the 5‐year period after endoscopic variceal ligation for esophageal variceal bleeding in an emergency setting. Child–Pugh C, alcoholic liver cirrhosis, and no follow‐up endoscopy increased the risk of rebleeding; Child–Pugh C, coexistence of hepatocellular carcinoma, and no follow‐up endoscopy increased the risk of mortality.